2018
DOI: 10.1016/j.matchar.2018.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of a сarbon-doped CoCrFeNiMn high-entropy alloy

Abstract: Butt-joint seam of a high entropy alloy (HEA) of the CoCrFeNiMn system was successfully obtained by friction stir welding (FSW). The HEA was produced by self-propagating high-temperature synthesis. Along with the principal elements, a small amount (0.9 at.%) of C was added to the alloy. The as-cast alloy was cold rolled and annealed at 900°C to produce refined microstructure. The structure of the annealed alloy consisted of a recrystallized face-centered cubic matrix with a grain size of 9.2 μm and fine Cr-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…The obtained results demonstrate for the first time the possibility to produce sound butt joints of the Ti 1.89 NbCrV 0.56 RHEA by LBW, which is an important step toward potential practical applications of this new class of metallic alloys. However, the present study also emphasized the importance of LBW process parameters (particularly pre-heating temperature) to obtain good results, which is quite different from the transition metals HEAs [27][28][29][30][31][32]44,45]. Given the wide range of the available RHEAs compositions [7], specific attention should be paid to select proper welding conditions for each individual alloy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The obtained results demonstrate for the first time the possibility to produce sound butt joints of the Ti 1.89 NbCrV 0.56 RHEA by LBW, which is an important step toward potential practical applications of this new class of metallic alloys. However, the present study also emphasized the importance of LBW process parameters (particularly pre-heating temperature) to obtain good results, which is quite different from the transition metals HEAs [27][28][29][30][31][32]44,45]. Given the wide range of the available RHEAs compositions [7], specific attention should be paid to select proper welding conditions for each individual alloy.…”
Section: Discussionmentioning
confidence: 84%
“…Weldability is another crucial technological property of the structural materials, since welding is one of the most reliable and efficient ways of joining different parts together. A few studies on welding of HEAs were reported recently [27][28][29][30][31][32]. The efficiency of using arc welding [28], laser beam welding (LBW) [31], electron beam welding [27,28], and friction stir welding [29,30,32] was shown to obtain sound joints in HEAs with reasonable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, welding materials in the solid state can be a reliable and advantageous way to achieve sound joints. The current information regarding welding HEAs using solid-state techniques shows that most studies are focused on friction stir welding (FSW) [55,[86][87][88][89][90][91][92]. Nevertheless, other possibilities for joining these materials are rotary friction welding [91] and diffusion bonding [92].…”
Section: Solid-state Welding Of Heasmentioning
confidence: 99%
“…After being produced via thermite-type self-propagating hightemperature synthesis, the samples were cold-rolled and annealed at 900 °C for 1 h, to obtain an equiaxed microstructure. The welds resultant from the FSW process were defect-free, while On another perspective, Shaysultanov et al [90] performed FSW on a carbon-doped CoCrFeNiMn HEA, with the intent of studying the influence this controlled C addition on the welded joints mechanical performance. After being produced via thermite-type self-propagating high-temperature synthesis, the samples were cold-rolled and annealed at 900 • C for 1 h, to obtain an equiaxed microstructure.…”
Section: Solid-state Welding Of Heasmentioning
confidence: 99%
“…Several works have studied the friction stir welding (FSW) of HEA systems [ 29 , 33 , 34 , 35 , 36 , 37 ]. Different from arc, laser and electron beam welding, FSW ( Figure 8 ) is a form of solid-state joining, in which two facing workpieces are jointed through the heat generated by friction between the rotating of a non-consumable tool and the workpiece material [ 38 ].…”
Section: Welding Of Heas In Different Welding Processesmentioning
confidence: 99%